SCHEDULING AND POWER DISTRIBUTION SYSTEM ON DIESEL POWER PLANT IN NORTH SULAWESI USING GENETIC ALGORITHM - Josephin Sundah (Jurnal Sistem Informasi, 2013)
Research regarding scheduling and power distribution system on diesel power plant in North Sulawesi using genetic algorithm has been done. This research was conducted to provide a new approach for scheduling and power distribution in North Sulawesi. Method of genetic algorithm is used in this study to address the problem of scheduling and distribution system of diesel power plant. Method of genetic algorithms is a heuristic search algorithm that mimics the mechanisms of biological system. Under this concept, the problem will be solved using the pattern of biological evolution. Solutions for solving problems will apply the method of selection, crossover, and mutation. Scheduling using genetic algorithm can optimize the scheduling done by by PT. PLN North Sulawesi, Minahasa System AP2B. Based on the results and the discussion it can be concluded that the genetic algorithm can be used as an efficient method for scheduling and power distribution system on the diesel power plants in North Sulawesi.